Change over time in interactions between unfamiliar toddlers. (January 2023) - Lahat, Ayelet; Perlman, Michal; Howe, Nina; Recchia, Holly E.; Bukowski, William M.; Santo, Jonathan B.; Luo, Zhangjing; Ross, Hildy
The frequency and length of games, conflicts, and contingency sequences that took place between toddlers as they got to know one another were studied using archival data. The sample consisted of 28 unfamiliar 20- and 30-month-old toddlers (predominantly White, 16 males) who met separately with each of two other toddlers for 18 play dates. The frequency of games increased over time, while the frequency of conflict and contingency sequences decreased. The length of games increased over time while the length of conflicts and contingency sequences were stable. Age and language ability predicted changes in frequency and length of the different types of sequences. Thus, toddlers engage in less structured interactions when they first meet; their interactions become increasingly more organized and positive as the relationship evolves.